Money Largely Accounts for Increased Unemployment during Stagflation, Shows a Recent Study - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2008)
Is there a relation between money, measured by inflation or interest rates, and unemployment? According to Aleksander Berensten, Guido Menzio and Randall Wright -- co-authors of a recent paper on “Inflation and Unemployment in the Long Run” -- there is a strong positive relation. Wright, who is professor of economics at Wharton, presented a seminar based on their paper at the Singapore Management University’s School of Economics.